2021
DOI: 10.3390/children8060432
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Genetical, Pre, Peri and Post Natal Risk Factors of Deciduous Molar Hypomineralization (DMH), Hypomineralized Second Primary Molar (HSPM) and Molar Incisor Hypomineralization (MIH): A Narrative Review

Abstract: Objectives: Analyze defects in the state of maturation of the enamel result in an adequate volume of enamel, but in an insufficient mineralization, which can affect both deciduous teeth and permanent teeth. Among the most common defects, we recognize Deciduous Molar Hypominerlization (DMH), Hypomineralized Second Primary Molar (HSPM), and Molar Incisor Hypomineralization (MIH). These, in fact, affect the first deciduous molars, the second deciduous molars and molars, and permanent incisors, respectively, but t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 45 publications
(102 reference statements)
2
32
0
14
Order By: Relevance
“…Butera et al observed a higher prevalence in children whose mothers had complications during pregnancy and delivery 8 . For Pitiphat et al there is a statistically significant relationship with cesarean delivery, complications during vaginal delivery, and also with serious or chronic diseases in children under 3 years of age 9 .…”
Section: Introductionmentioning
confidence: 97%
“…Butera et al observed a higher prevalence in children whose mothers had complications during pregnancy and delivery 8 . For Pitiphat et al there is a statistically significant relationship with cesarean delivery, complications during vaginal delivery, and also with serious or chronic diseases in children under 3 years of age 9 .…”
Section: Introductionmentioning
confidence: 97%
“…The presence of enamel hypomineralization resulting from disturbances during matrix formation stage of enamel development increases the risk of dental caries both in primary and permanent dentition, thereby affecting a child’s quality of life [ 2 , 9 , 10 , 11 , 12 , 13 , 14 ]. These defects result from systemic, genetic or environmental factors and recent systematic reviews highlighted the influence of PTLBW on these enamel defects [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 20 ]. The prevalence of PTLBW is high among the Indian population because of low nutritional status [ 31 , 32 ], yet there is a lack of prospective studies at the population level to estimate the influence of PT-LBW with the prevalence of EH in primary teeth and MIH.…”
Section: Discussionmentioning
confidence: 99%
“…Enamel hypomineralization (EH) in primary teeth and molar incisor hypomineralization (MIH) in permanent teeth are qualitative defects of enamel resulting from disturbances during the matrix formation stage of enamel development [ 1 , 2 , 3 ]. The etiologies of EH and MIH are considered multifactorial and may be influenced by systemic, genetic and or environmental factors, which include premature birth, underweight birth, infections, hypoxia, malnutrition, or metabolic disorders, and are often reported in higher frequency among low socioeconomic families [ 4 , 5 , 6 , 7 , 8 , 9 ]. These hypomineralized areas are responsible for considerable esthetic problems, hypersensitivity of involved teeth and predisposition to dental caries both in primary and permanent dentition, affecting children’s quality of life [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, it manifests as white, yellow, or brown spot lesions on the surface of the permanent molars or/and incisors, visible during tooth eruption [ 1 ]. The pathogenesis of MIH, which has been defined as a complex condition, has been thoroughly investigated by a number of researchers [ 2 , 3 , 4 ]. Potential causal factors are divided into three groups: prenatal, perinatal, and postnatal.…”
Section: Introductionmentioning
confidence: 99%